Application of the contingent valuation method for the ‎estimation of the economic value of the heritage of Tlemcen park - Yamina Necissa; Naima Chabbi Chemrouk (Dirassat Journal Economic Issue, 2020)
The analysis of the economic value of heritage consists in determining the monetary values lent to use values as well as to existence values.In the case of the heritage of Tlemcen Park, the values resulting from the use of this heritage are not available in monetary form.  The definition of economic value was therefore based on the willingness to pay of users to benefit from cultural heritage services.This article presents the results of an economic study carried out to measure the economic value of the cultural heritage of Tlemcen Park. The survey allowed us to determine the attachment relationship of the inhabitants of Tlemcen to the cultural heritage, and finally, to verify the existence of a willingness to pay for its development.